Water Management “Tabat System” in Carbon Dioxide Mitigation and Vulnerability to Fire On Peatland - Siti Nurzakiah; . Nurita; Dedi Nursyamsi (UNIVERSITY OF LAMPUNG, 2016)
The conservation measures of peat or peat maintain under natural conditions many proposed to address the increase in carbon emissions from land use change and efforts to minimize of fire, but it can not entirely implemented due to peat land has the potential for development of the agricultural commodities is supported by extensive area. Peatlands can be productive agricultural land with appropriate methods. Water management is required to regulate groundwater levels which is suitable for plants, nature conservation and restore hydrological conditions, such as reducing the vulnerability to fire. The percentage of water content vertically and functional groups of organic materials that have both hydrophilic and hydro phobic properties can be an indicator of vulner ability to fire. This research was conducted by survey method and then field sampling on land use rubber. Water management carried out with the installation of water-gate in the drainage channels (Tabat System). There are two experimental units in peatland, namely: 1) the drainage channel is equipped with the water-gate/Tabat (KST), Tabat size adjusted to the channel dimensions, and 2) there are no water-gate on the drainage channel (KNT). The parameters are observed of CO2 fluxes, ground water levels, water content and functional groups of organic matter. The purpose of this study was to determine the role of “tabat system” in mitigating CO2 emission sand vulner ability tofire. The results showed that the water management “tabat system” can reduce CO2 emissions by 47.6%, reducing hydrophobic properties of peat (0-50 cm soil depth) of 6.6% and is able to prevent loss of water-holding ability of fibric peat by 26.6%. This indicates that water management measures is required as one effort to maintain of peat to remain moist condition, so that changes in peat properties of hydrophilic become hydrophobic can be prevented, and reduce peat vulnerability to fire.Keywords: Carbon dioxide emissions, Peatland, Vulner ability to fire, Water management [How to Cite: Siti Nurzakiah, Nurita and Dedi Nursyamsi. 2016. Water Management “Tabat System” in Carbon Dioxide Mitigation and Vulnerability to Fire On Peatland. J Trop Soils 21: 41-47. Doi: 10.5400/jts.2016.21.1.41]